Repairing slight damages on monocrystalline silicon surface by thermal annealing. (9th April 2021) - Feng, Chengqiang; Wu, Lei; Chen, Peng; Yang, Tingting; Yu, Bingjun; Qian, Linmao
Abstract: The damages on silicon substrate, usually caused by machining and polishing processes, inevitably degrade the mechanical and electrical properties of the devices involved. Defect-free silicon substrates are essential with the miniaturization of integrated circuits to tens of nanometers, and repairing the damages is significant for manufacturing excellent devices. In this study, the slight damages, i.e. protrusive hillocks resulting from nanoscratching on monocrystalline silicon surface, was thermally annealed in vacuum for repairing, and groove-shaped scratches were also annealed for comparative study. In-situ topographies of the hillocks before and after the annealing were detected with an atomic force microscope (AFM), and then compared for finding the optimum annealing temperature. It is shown that the protrusive hillocks can be well repaired than the groove-shaped scratches. The repairing with annealing process was further verified by conductive AFM detection and selective etching in hydrofluoric acid solution. Raman spectroscopy detection was employed to clarify the annealing-dependent recovering mechanism of the damages on silicon surface, and it is suggested that structural transformation plays an important role in the repairing. In addition, the annealing of the hillocks on single-crystal quartz surface confirmed the structural recovery rather than the oxidation during annealing.